An Indian Case Study on Mitochondrial Neurogastrointestinal Encephalomyopathy - Shabana Kareem; Reemy Sara Mathai (Archives of Medicine and Health Sciences)
Mitochondrial neurogastrointestinal encephalomyopathy (MNGIE) is a unique autosomal recessive disorder characterized by mitochondrial changes resulting from mutations in the TYMP gene, responsible for encoding thymidine phosphorylase. Despite its genetic origin, the study indicates that the manifestation of MNGIE does not strictly adhere to a hereditary pattern. The investigation focused on a family from the Ernakulam district of Kerala, India, involving three members. The proband began experiencing gait difficulties at the age of 4, leading to a confirmed diagnosis of MNGIE at 17. Subsequent clinical assessments confirmed MNGIE in the two younger siblings, while the youngest remained unaffected. Common symptoms across all three included ptosis, limited eye movements, generalized muscle atrophy, and the absence of tendon reflexes. Elevated lactate levels were observed in both venous blood and cerebrospinal fluid, and magnetic resonance imaging scans revealed diffuse leukoencephalopathy. Emphasizing the importance of early identification of MNGIE patients, the study underscores the emerging therapeutic options that can positively impact survival and overall health outcomes. The findings highlight that prompt diagnosis and intervention contribute to improved prognosis and well-being in affected individuals.